Understanding the Relation with Nature in the City: Biodiversity Knowledge and Environmental Awareness in a Periurban Area of Quito, Ecuador - Morales-Espín, Belén (2022)
The development of ecological sustainability within cities requires raising awareness among citizens of the importance of biodiversity for their daily lives. We evaluated the biodiversity awareness of high school students and their families, working with two schools in Guayllabamba, part of the Metropolitan District of Quito, Ecuador. A total of 405 people answered a survey to evaluate their knowledge about basic biological concepts, urban biodiversity and environmental awareness. People in Guayllabamba have some biodiversity knowledge, mainly for domestic or human-related species, with emphasis on those with direct human uses (food and medicine). The surveyed citizens showed a positive environmental awareness attitude, they consider biodiversity important and use it in their lives. However, we identified gaps in which environmental education should focus for clarifying concepts like “endemic”, “native” or “wild”. Ecosystem contribution of biodiversity is neither well understood. Our results point out AN utilitarian knowledge of nature that can be related to a periurban area where agriculture and farmland still have important presence, and where the daily contact with biodiversity remains. The reinforcement of biological awareness driven by environmental education may be a key component to promote environmentally friendly urban development in the area.